Atividade Leishmanicida do Extrato Etanólico Bruto de Croton blanchetianus Bail - Pereira, Katily Luize Garcia (2014)
Leishmaniasis is a complex of parasitic diseases caused by protozoa of the genus Leishmania and transmitted to humans and other vertebrate hosts through the bite of an infected phlebotomine insect. Currently, all drugs used in the treatment of this disease have low efficacy, high toxicity and are associated with parasitic resistance. In this sense, scientific research that indicates a new compounds with leishmanicidal activity are quite promising. The objective of this study was to evaluate in vitro the leishmanicidal activity of the crude ethanol extract of C. blanchetianus on L. amazonensis and L. infantum as well as their toxic and immunomodulator effect on murine macrophages. Promastigotes in the logarithmic growth phase were subjected to treatment with different concentrations of the extract for 24 and 72 hours at 26ºC, and the viability was measured by the method of Alamar Blue . A greater inhibition was observed in L. amazonensis with an IC50 of 73.6 μg/ml in 24 hours of incubation and 42.6 μg/ml at 72 hours. In L. infantum extract showed an IC50 of 208.7 μg/ml in 24 hours and 108.9 μg/ml at 72 hours. Regarding the reduction of viability, L. amazonensis showed a death percentage of 68.8% with 100 μg/ml of the extract after 24 hours of treatment and approximately 100% after 72 hours, whereas for L. infantum this level of inhibition was not seen with 250 μg/ml of the extract. For the analysis of antiamastigota activity, infected macrophages were treated with different concentrations of the extract and incubated for 72h at 37° C, and the rate of infection was determined by staining method with hematologic pigment and counts in optical microscopy. It was found a higher dose-dependent inhibition in L. amazonensis with an IC50 of 3.10 μg/ml. In L. infantum there was a lower activity of the extract which present an IC50 of 8.83 μg/ml. At lower concentration tested (3 μg/ml) there was a reduction in the viability of L. amazonensis around 44%, while in L. infantum, this level of inhibition was only observed with 7 μg/ml of extract. The cytotoxicity was performed on murine macrophages incubated with different concentrations of the extract for 72 hours at 37°C and the viability was measured by Alamar Blue method. The LD50 observed was 83.79 μg/ml and the selectivity index calculated was 27 to L. amazonensis and 9.5 for L. Infantum, revealing a higher toxicity of the extract in the parasites than in macrophages.Treatment with the extract not modulated the macrophage for nitric oxide synthesis, as verified by Griess reaction. However, interfered in the morphology of promastigote forms, being observed parasites with a rounded body and/or double scourge. Therefore, the data presented in this study indicate that the ethanol extract of C. blanchetianus presents leishmanicidal activity on promastigote and amastigote forms of L. amazonensis and L. infantum, being more effective against the species L. amazonensis, especially on the amastigote form, without causing, however, toxicity to the host cell.